Extracorporeal Organ Support for Burn-Injured Patients - Garrett W. Britton; Amanda R. Keith; Barret J. Halgas; Joshua M. Boster; Nicholas S. Niazi; Kevin K. Chung; Leopoldo C. Cancio (MDPI AG, 2024)
As mortality relating to severe acute burn injury improves, patients are surviving longer into the critical care phase, which is commonly complicated by multisystem organ failure. Extracorporeal organ support (ECOS) represents a set of potential therapeutic technologies for managing patients with organ-specific complications. This article provides a comprehensive review of the existing literature, focusing on the use of continuous kidney replacement therapy, extracorporeal membrane oxygenation, extracorporeal carbon dioxide removal, and extracorporeal blood purification. Though promising, many of these technologies are in the early phases of implementation and are restricted to well-resourced medical systems, limiting their use in large scale casualty and austere scenarios.